Cloning of a subunit of yeast RNA polymerase II transcription factor b and CTD kinase. - Gileadi, O; Feaver, W; Kornberg, R (1992)
Yeast RNA polymerase II initiation factor b copurifies with three polypeptides of 85, 73, and 50 kilodaltons and with a protein kinase that phosphorylates the carboxyl-terminal repeat domain (CTD) of the largest polymerase subunit. The gene that encodes the 73-kilodalton polypeptide, designated TFB1, was cloned and found to be essential for cell growth. The deduced protein sequence exhibits no similarity to those of protein kinases. However, the sequence is similar to that of the 62-kilodalton subunit of the HeLa transcription factor BFT2, suggesting that this factor is the human counterpart of yeast factor b. Immunoprecipitation experiments using antibodies to the TFB1 gene product demonstrate that the transcriptional and CTD kinase activities of factor b are closely associated with an oligomer of the three polypeptides. Photoaffinity labeling with 3'-O-(4-benzoyl)benzoyl-ATP (adenosine triphosphate) identified an ATP-binding site in the 85-kilodalton polypeptide, suggesting that the 85-kilodalton subunit contains the catalytic domain of the kinase.